Painting and Performance: the Protagonism of Corporeal Action in Creative Processes (Revista Apotheke, 2025)
This article aims to analyze the production of performance art in the dialogue between the body and visual arts. It starts from the understanding that the body, as an expressive and active agent, can play a fundamental role in artistic creation processes, not only as an instrument but as a presence that imprints gestures and internationalities on the materiality of the work. To build the theoretical foundation of this investigation, the research drew on some theoretical contributions, such as the studies of Renato Cohen, regarding the understanding of performance as an artistic language; Leda Maria Martins, whose notion of gesture is explained as inscriptions of cultural knowledge; Jorge Glusberg, for the historical understanding of the relationship between visual arts and performance; and Gilles Deleuze, in the sense of perceiving the body as a creative force and a generator of meanings. Regarding the methodological path, two categories of analysis were mobilized: body as support and body as mediation. From the observed creative processes, the strength of gesture, movement, and the presence of the body in the construction of the image became evident. The research noted, in its final considerations, a shift of focus toward the creation process, paying attention to the marks, repetitions, and bodily variations that manifest themselves throughout the production, while respecting the particularities of each artist. Also, in the process of hybridization between performative and pictorial language, the body emerges as a protagonist and an indispensable agent in the elaboration of artistic work.
Keywords: painting; performance; body; gesture; materiality